Different audiometric findings with different symptoms for diagnosing superior semicircular canal dehiscence symptoms: a retrospective study of 12 cases - Meliha Başöz Behmen; Selahattin Tuğrul; Ozlem Konukseven (The Egyptian Journal of Otolaryngology)
Abstract Background Due to the patients with no symptoms for dehiscence but having audiological different findings who came to clinic, this study aims to evaluate the audiological characteristics of 12 cases diagnosed with superior semicircular canal dehiscence and to compare the findings with the literature. Methods We evaluated a case-series of 12 cases aged 11–59 years with a pre-diagnosis of semicircular canal dehiscence (SSCD) by clinical history and audiological evaluation between 2019 and 2022 and a final diagnosis by high-resolution computed tomography. Audiological evaluation includes air-bone conduction and speech audiometry, tympanometry, and acoustic reflex test. Results Unilateral dehiscence was observed in 6 cases, and bilateral dehiscence was observed in the other 6. Considering types of hearing loss, we observed 5 normal hearing, 1 mixed type, 2 conductive type, and 4 sensorineural type. Also, numerous clinical characteristics were observed: vestibular complaints (9/12), chronic imbalance (9/12), Tullio phenomenon (6/12), Hennebert sign (6/12), and tinnitus (5/12). Patients with symptoms no audiological findings and patients with audiological findings no symptoms were seen with dehiscence diagnosis. Conclusion Various symptoms and findings were observed in patients with semicircular canal dehiscence. While patients with no symptoms for diagnosing dehiscence are presented, audiological findings with low-frequency hearing loss and air–bone gap can be landmark. In addition, patients with SSCD symptoms, even if they do not have audiometric findings, should be further evaluated with radiological evaluation.